2019
DOI: 10.3390/ani9080505
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Grain Yield, Straw Yield, Chemical Composition, Carbohydrate and Protein Fractions, In Vitro Digestibility and Rumen Degradability of Four Common Vetch Varieties Grown on the Qinghai-Tibetan Plateau

Abstract: Four varieties of common vetch, including three improved varieties (Lanjian No. 1, Lanjian No. 2, and Lanjian No. 3) and one local variety (333A), were evaluated for varietal variations in grain yield, straw yield and straw quality attributes on the Qinghai-Tibetan Plateau. Crops were harvested at pod maturity to determine grain yield, straw yield, harvest index, and potential utility index (PUI). Straw quality was determined by measuring chemical composition, carbohydrate and protein fractions, in vitro gas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(102 reference statements)
1
6
1
Order By: Relevance
“…Significant differences in stover quality appear to relate to varietal variations in accumulation and lignification of cell wall contents, and the leaf to stem ratio. Others have reported similar results in common vetch [1,24] and faba bean (Vicia faba L.) [25]. With the exception of variety 333A, stover CP and IVOMD of all improved varieties exceeded 120 g/kg DM and 517 g/kg OM, respectively.…”
Section: Stover Chemical Composition and In Vitro Characteristicssupporting
confidence: 61%
“…Significant differences in stover quality appear to relate to varietal variations in accumulation and lignification of cell wall contents, and the leaf to stem ratio. Others have reported similar results in common vetch [1,24] and faba bean (Vicia faba L.) [25]. With the exception of variety 333A, stover CP and IVOMD of all improved varieties exceeded 120 g/kg DM and 517 g/kg OM, respectively.…”
Section: Stover Chemical Composition and In Vitro Characteristicssupporting
confidence: 61%
“…The range of 68.4 to 75.6% of IVOMD recorded in this study for different forages of S. scabra accessions indicate good digestibility of forages despite the fact that accessions were harvested at maturity. The calculated value for ME in present study were observed to be higher than those of Avena sativa L. and Vicia sativa L. as reported by Kafilzadeh and Heidary [ 43 ] and Huang et al [ 44 ], respectively. However, they were in the range of values for alfalfa hay as recorded by Abas et al [ 45 ].…”
Section: Discussioncontrasting
confidence: 46%
“…1) and an early maturing (Lanjian No. 3) common vetch cultivars were chosen as the superior commercial cultivars presently grown at the research site 5,20 . Crops were sown by hand at a density of 150 viable seeds per square meter, with four replicates per cultivar in a completely randomized design.…”
Section: Methodsmentioning
confidence: 99%
“…However, the banning of meat meal in ruminant diets in the EU 2 as well as in other regions of the world magnifies the pressure on livestock farmers to produce home‐grown alternative high‐protein forages. The use of common vetch in grassland‐livestock systems has expanded greatly in many countries of the world, 3–5 partly for its good suitability for planting where other annual legumes 6 or perennial forage legumes 7 are poorly cultivated, but also because it is a high‐concentration protein forage crop 8,9 with the potential for use across a range of livestock classes. However, the optimal use of common vetch forages demands a suitable synchronization of forage nutritional composition with the nutrient requirements of each livestock class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation